ALAT PENGHITUNG OTOMATIS PEMILIHAN SUARA BERBASIS MIKROKONTROLER ATMEGA 32 - , RIO AJI SAPUTRA R ([Yogyakarta] : Universitas Gadjah Mada, 2014)
âALAT PENGHITUNG OTOMATIS PEMILIHAN SUARA BERBASIS MIKROKONTROLER ATMEGA32â give priority to the safety and convenience with a quick calculation, because the sound goes directly processed ATMega AVR microcontroller 32, in addition to security and fast calculation tool also has the advantage of reducing the number of abstentions or white group, eliminating the election of two times or more in opportunities by providing limited time for participants voters, eliminating the problems in the ballot paper is damaged, the tool can be used more than once in a way to reset back tool but data taken from previous calculations will be lost, to avoid any manipulation of the data results from the previous calculation . LED indicators able to signal to participants if the emphasis on the pushbutton has been done then the LED will die, while the committee can immediately see through 16x2 LCD display located on the back side of the tool, so that the number of fraud will be reduced, the election can be terminated at any time by pressing a certain key on the keypad 3x4 that is in the back side of the tool. After the suppression is done, the calculation will be stopped, the LED indicators are off, and the LCD displays the results of the election.